2017
DOI: 10.1186/s12909-017-0928-x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and efficacy of implementing a focused cardiac ultrasound course into a medical school curriculum

Abstract: BackgroundTeaching cardiac ultrasound to medical students in a brief course is a challenge. We aimed to evaluate the feasibility of teaching large groups of medical students the acquisition and interpretation of cardiac ultrasound images using a pocket ultrasound device (PUD) in a short, specially designed course.MethodsThirty-one medical students in their first clinical year participated in the study. All were novices in the use of cardiac ultrasound. The training consisted of 4 hours of frontal lectures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Furthermore, after training, medical students can adequately interpret images with a very simplified or binary assessment [36]. A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39]. Four other studies used a point-of-care ultrasonography training program to determine diagnostic performance in various clinical scenarios [36,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after training, medical students can adequately interpret images with a very simplified or binary assessment [36]. A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39]. Four other studies used a point-of-care ultrasonography training program to determine diagnostic performance in various clinical scenarios [36,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, training in FoCUS was provided on live patients and relied on direct oversight from expert sonographers or echocardiographers to provide instruction and to assess their competence. For example, Kobal et al 9 demonstrated that medical students improved in view acquisition after brief training under the guidance of trained experts; assessment was based on instructor review of acquired images using a checklist. However, instructor review of images is time consuming and labor intensive, and checklists are subject to inter‐rater variability 20 …”
Section: Discussionmentioning
confidence: 99%
“…This model of teaching basic cardiac ultrasound is rapidly becoming untenable as faculty time for one‐on‐one training and assessment of student progress is limited. Previous studies have developed FoCUS curriculum led by experts (board and society certified echocardiographers and sonographers) to instruct students in both FoCUS view acquisition and interpretation of normal images and pathologic findings 9,10 . To better optimize expert time and educational experience, we posit that the basics of view acquisition can be learned via simulator with objective measures to ensure baseline skill, thereby reserving expert time to the more advanced skills required for FoCUS image interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that even students receiving brief training in focused echocardiography can reach good diagnostic accuracy in a limited but relevant range of cardiac pathologies [45,46]. The number of studies necessary to obtain competence in bedside echocardiography is debatable.…”
Section: Trainingmentioning
confidence: 99%